2017
DOI: 10.1007/s10518-017-0218-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coupling excess pore pressure and soil deformation on nonlinear SSI in liquefiable soil deposits

Abstract: The current seismic design philosophy is based on nonlinear behavior of structures where the foundation soil is often simplified by a modification of the input acceleration depending on the expected site effects. The latter are generally limited to depend on the shear-wave velocity profile or a classification of the site. Findings presented in this work illustrate the importance of accounting for both soil nonlinearity due to seismic liquefaction and for soilstructure interaction when dealing with liquefiable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Changes in pore structure are considered a fundamental factor influencing the macroscopic mechanical properties of soils [15,16]. Skvortsova et al [17] contend that under external environmental influences, soil structure is complex and dynamic, making the geometry of the pore space a crucial indicator of the soil's structural state.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in pore structure are considered a fundamental factor influencing the macroscopic mechanical properties of soils [15,16]. Skvortsova et al [17] contend that under external environmental influences, soil structure is complex and dynamic, making the geometry of the pore space a crucial indicator of the soil's structural state.…”
Section: Introductionmentioning
confidence: 99%
“…e first limitation has to do with the soil-structure interaction (SSI) phenomenon, which is disregarded by several seismic codes along with the regular everyday structural practice, presuming that lack of this phenomenon causes conservative outcomes [2][3][4][5][6]. In the related articles, several investigations approve the great impacts of SSI [7][8][9][10][11]. In this way, observations and examinations from real samples and also analyses have demonstrated that structures based on flexible soil display importantly other seismic responses than that of structures setup on solid rock caused by the substitution of the dynamic features of the system.…”
Section: Introductionmentioning
confidence: 99%